Plastics Meet Their Nemeses: Exploring the Role of Plastic Eating Fungi - Sharma, Debjeet; Gupta, Dharmesh; Sharma, Pratibha; Sharma, Shubham (Chronicle of Bioresource Management, 2025)
Plastics take generations to naturally break down because of their chemical makeup, which causes a huge buildup of plastic trash in the environment. Since they use enzymes they release into their surroundings to break down organic matter, fungus are essential decomposers in natural environments. Researchers have recently found that some fungi can decompose far more difficult materials, such as plastic. Enzymes like hydrolases, laccases, and peroxidases are produced by these decomposer fungus and are capable of breaking down the lengthy polymer chains present in plastics. They break down complicated materials like wood using a similar process. The scientific community is very interested in using these fungi to break down plastic trash because of their special capabilities. Utilizing fungi that consume plastic has a lot of potential for trash management.